2021
DOI: 10.1111/iej.13595
|View full text |Cite
|
Sign up to set email alerts
|

Five decades of the International Endodontic Journal: Bibliometric overview 1967–2020

Abstract: Aim The International Endodontic Journal (IEJ) has served as a platform for research and clinical practice in Endodontics since 1967. This study provides a bibliographic analysis and overview of the publications that have appeared in the IEJ from 1967 to 2020. Methodology A literature search was performed in Elsevier's Scopus database to locate all the publications of the International Endodontic Journal. Various bibliometric software packages including the open‐source visualization software Gephi and Bibliosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 79 publications
(62 reference statements)
1
28
0
Order By: Relevance
“…While acknowledging the relationship between article age and citations, where cross‐sectional studies demonstrate higher citations accrued by older articles (Khan et al, 2021; Ordinola‐Zapata et al, 2020; Yilmaz et al, 2019), this study identified other factors that predict citations: the type of article, publication in an IF journal and presence of an AAS. Narrative reviews were associated with the highest citations in unadjusted and adjusted models, a finding consistent with orthodontic research articles (Doğramacı & Rossi‐Fedele, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While acknowledging the relationship between article age and citations, where cross‐sectional studies demonstrate higher citations accrued by older articles (Khan et al, 2021; Ordinola‐Zapata et al, 2020; Yilmaz et al, 2019), this study identified other factors that predict citations: the type of article, publication in an IF journal and presence of an AAS. Narrative reviews were associated with the highest citations in unadjusted and adjusted models, a finding consistent with orthodontic research articles (Doğramacı & Rossi‐Fedele, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…The term “bibliometrics” was first coined by Pritchard (1969) as “the application of mathematics and statistical methods to books and other media of communication”, where their usage are counted, analysed and interpreted. Several research groups, in recent years, have applied various methods to investigate different bibliometrics in Endodontology, reporting on major research themes, study designs, number of manuscripts published in different journals, institutional affiliations and geographic origin of major contributors and key collaborations, alongside citation analyses (Ahmad et al, 2019; Ahmad & Elgamal, 2020; Khan et al, 2021; Ordinola‐Zapata et al, 2020; Tzanetakis et al, 2015; Yilmaz et al, 2019). These studies have reported that most of the literature originates from either the US or Brazil, is largely original research focussed on endodontic materials, with the majority of publications appearing in either the International Journal of Endodontics or Journal of Endodontics , with over a dozen “classic” articles (having 400 or more citations) being identified.…”
Section: Introductionmentioning
confidence: 99%
“…All articles in this study were published in 134 journals, 13 of which were with more than 10 articles published ( Figure 2C ) . The impact factor (IF) and journal quartile were obtained from Journal Citation Reports 2020 ( 23 ). The top 3 prolific journals were European Journal of Nuclear Medicine and Molecular Imaging (IF9.236), Frontiers in Oncology (IF6.244), and Cancers (IF6.639).…”
Section: Resultsmentioning
confidence: 99%
“…Nickel‐titanium ranked as no. 6 among the most frequently used key words in the IEJ (Khan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%